MARKETING STRATEGY ANALYSIS IN INCREASING PRODUCT SALES AT LAKITA CELL IN MAKASSAR CITY - Syamril; Parawansa, Dian Anggraece Sigit; Mustafa, Fahrina (CV. Radja Publika, 2023)
Strategy is a tool to achieve objectives. Marketing is a process influenced by various social, cultural, political, economic, and managerial factors. There are three systematic marketing strategy steps, starting with market segmentation strategy, target market determination strategy, and market positioning strategy. The marketing mix also includes marketing strategies, comprising four crucial points: product, price, place, and promotion. The purpose of this research is to analyze marketing strategies in increasing product sales at Lakita Cell in the city of Makassar. This study adopts a qualitative research design. Primary and secondary data sources are utilized for data collection. Data collection techniques consist of observation, interviews, and documentation. Data analysis involves three stages: data collection, data analysis, and decision-making. The research findings indicate that segmentation influences sales levels due to varying network quality in each area, while targeting does not significantly affect profits as sales levels fluctuate. Positioning has a significant impact on sales, profits, and company growth as Lakita Cell not only focuses on internet voucher sales but also provides services like interbank ATM transfers, digital money top-ups, and various types of mobile phone and electronic device essentials.